Targeted plasma metabolic profiles and risk of recurrence in stage II and III colorectal cancer patients: results from an international cohort consortium - Ose, Jennifer; Gigić, Biljana; Brezina, Stefanie; Lin, Tengda; Baierl, Andreas; Geijsen, Anne J. M. R.; van Roekel, Eline; Robinot, Nivonirina; Gicquiau, Audrey; Achaintre, David; Keski-Rahkonen, Pekka; van Duijnhoven, Fränzel J. B.; et al. (Metabolites, 2021)
The identification of patients at high-risk for colorectal cancer (CRC) recurrence remains an unmet clinical need. The aim of this study was to investigate associations of metabolites with risk of recurrence in stage II/III CRC patients. A targeted metabolomics assay (128 metabolites measured) was performed on pre-surgery collected EDTA plasma samples from n = 440 newly diagnosed stage II/III CRC patients. Patients have been recruited from four prospective cohort studies as part of an international consortium: Metabolomic profiles throughout the continuum of CRC (MetaboCCC). Cox proportional hazard models were computed to investigate associations of metabolites with recurrence, adjusted for age, sex, tumor stage, tumor site, body mass index, and cohort; false discovery rate (FDR) was used to account for multiple testing. Sixty-nine patients (15%) had a recurrence after a median follow-up time of 20 months. We identified 13 metabolites that were nominally associated with a reduced risk of recurrence. None of the associations were statistically significant after controlling for multiple testing. Pathway topology analyses did not reveal statistically significant associations between recurrence and alterations in metabolic pathways (e.g., sphingolipid metabolism p = 0.04; pFDR = 1.00). To conclude, we did not observe statistically significant associations between metabolites and CRC recurrence using a well-established metabolomics assay. The observed results require follow-up in larger studies.
Gesehen am 18.07.2021